Hand-held total ozone column concentration measurements in the Philippines - Macatangay, Ronald (Animo Repository, 2013)
In this study, total ozone column (TOC) concentrations were measured from the ground using the hand-held Microtops II Ozone Monitor and Sunphotometer in the Philippines from February to November 2011, October and December 2012 and January 2013. Daily averages of TOC were compared to the data retrieved from the NASA Earth Obseving System (EOS) Aura satellite platform equipped with the Ozone Monitoring Instrument (OMI) and from the ESA Environmental Satellite (Envisat) using the SCanning Imaging Absorption spectroMeter for Atmospheric CHartographY (SCIAMACHY) instrument. Measurements of the total ozone column concentrations by a hand-held instrument show good agreement with satellite data during low aerosol optical thickness (AOT) and low cloud fraction conditions. Aerosols and clouds affect the accuracy of hand-held TOC measurements while solar targeting affects its precision. The bias introduced by aerosols and clouds depends on aerosol and cloud types. Precision in the hand-held measurements was improved when the instrument was mounted to a tripod. The Microtops II, OMI and SCIAMACHY datasets depicted the variability of the total column ozone with passing high and low pressure systems as indicated with the decrease of TOC with surface pressure. Transport processes occurring in the lower stratosphere dictate day-to-day variations in the total ozone column. Hand-held ozone measurements using the Microtops II Ozone Monitor and Sunphotometer provide a cheap yet comparable ground-based platform to space-borne observations of the total ozone column necessary for continuously monitoring ozone concentrations in the face of increased greenhouse gases in the atmosphere.